Sales and Production Management System and Reporting using Centralized Database System - Pigera A.I.H.; Senarathna P.P; D.L.H.S.D. Dodanduwa; G.A.M.T.S.B. Amarakoon; D. I .De Silva; Samitha Vidhanaarchchi (International Journal of Engineering and Management Research, 2022)
In the industry, one of the most extensively utilized systems is the Sales and Production management system. Since there were numerous departments inside the company, building up a shared sales and production management system enabled timely and effective control of the company's stocks, order management, and efficient use. If you do the accounting using manual methods for the administration, as mentioned above, chores will also take a lot of paperwork and workforce. This study suggests a system.